2023
DOI: 10.12659/msm.938892
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health-Related Quality of Life and Mental Health in 729 Medical Students in Indonesia During the COVID-19 Pandemic

Abstract: Background:The coronavirus disease 2019 (COVID-19) pandemic has impacted the health-related quality of life (HRQoL) and mental health worldwide. However, its impact on medical students in Indonesia has not been well documented. This study aimed to evaluate HRQoL and mental health in 729 Indonesian medical students during the COVID-19 pandemic. Material/Methods:We conducted a cross-sectional study from 31 August to 30 September 2021. The study instrument was an online questionnaire that was distributed via soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
5
0
2
Order By: Relevance
“…Appropriate sports exercise can promote students' mental health while enhancing physical fitness (Shen et al, 2024), and in terms of the correlation of physical activity on psychological factors of college students, there is no correlation between exercise time and both anxiety and depression. There are two views in existing research on the relationship between exercise duration and anxiety and depression, one view is that exercise duration is the only significant predictor of anxiety reduction through exercise (Patin et al, 2023), and that 20-40 minutes and 75 minutes of aerobic exercise improves anxiety and depression (Yan et al, 2022), respectively, however, the other view is opposite (Nugraha et al, 2023), and those who participated in 10 minutes of exercise had higher levels of anxiety compared to the results of the present agree with the latter view that the duration of exercise does not correlate with anxiety and depression in university students, and is largely based on the effect of exercise frequency. Some studies have shown that anxiety and depression improve with regular exercise, but few people currently engage in regular physical activity for a long period (de Sá et al, 2023), and college students after the COVID-19 pandemic, who felt mentally drained by the various campus epidemic prevention and control measures, were more emotionally sensitive and anxious than usual (Gu et al, 2023), and few students were able to engage in a certain amount of physical activity for a long period, and thus, in one-time physical activity, which has a very short-lived, if any, favourable effect (Massey et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate sports exercise can promote students' mental health while enhancing physical fitness (Shen et al, 2024), and in terms of the correlation of physical activity on psychological factors of college students, there is no correlation between exercise time and both anxiety and depression. There are two views in existing research on the relationship between exercise duration and anxiety and depression, one view is that exercise duration is the only significant predictor of anxiety reduction through exercise (Patin et al, 2023), and that 20-40 minutes and 75 minutes of aerobic exercise improves anxiety and depression (Yan et al, 2022), respectively, however, the other view is opposite (Nugraha et al, 2023), and those who participated in 10 minutes of exercise had higher levels of anxiety compared to the results of the present agree with the latter view that the duration of exercise does not correlate with anxiety and depression in university students, and is largely based on the effect of exercise frequency. Some studies have shown that anxiety and depression improve with regular exercise, but few people currently engage in regular physical activity for a long period (de Sá et al, 2023), and college students after the COVID-19 pandemic, who felt mentally drained by the various campus epidemic prevention and control measures, were more emotionally sensitive and anxious than usual (Gu et al, 2023), and few students were able to engage in a certain amount of physical activity for a long period, and thus, in one-time physical activity, which has a very short-lived, if any, favourable effect (Massey et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…As prevalências mais frequentes (60,1% a 70%) com 30,55% dos estudos, consolidando-se uma alta apresentação de estudantes com transtornos de ansiedade durante o período da pandemia do COVID-19 (Avila-Carrasco et al, 2023;Bhandari et al, 2022;Bintabara et al, 2024;Essangri et al, 2021;Gao et al, 2021;Guo, Crum e Fowler, 2021;Halperin et al, 2021;Nugraha et al, 2023;Paz et al, 2023;Safa et al, 2021;Soltan;Soliman;Dawoud., 2021). Nesse sentido, é importante destacar uma revisão sistemática realizada previamente ao período pandêmico que analisou a prevalência global de ansiedade entre estudantes de medicina, concluindo que 33,8% dos estudantes foram afetados por essa condição (Tian-Ci Quek et al, 2019).…”
Section: Discussionunclassified
“…Com relação aos fatores associados, no índice dos mais afetados, destaca-se as estudantes mulheres, apresentando em 50% dos artigos escolhidos (Alharthi et al, 2023;Çimen et al, 2022;Essangri et al, 2021;Ewid et al, 2023;Gao et al, 2021;Halperin et al, 2021;Huarcaya-Victoria et al, 2023;Johns;Waddington;Samuel, 2022;Jupina, Sidle e Rehmeyer Caudill., 2022;Kheirallah et al, 2021;Lee et al, 2021;Mirilović, Janković e Latas, 2022;Nakhostin-Ansari et al, 2020;Nugraha et al, 2023;Paz et al, 2023;Peng et al, 2023;Perissotto et al, 2021;Soltan, Soliman e Dawoud., 2021;Souza et al, 2022;Teh et al, 2023;Yeo et al, 2023;Yin et al, 2021). Nesta óptica, é necessário entender que esse público apresenta uma maior aptidão as alterações mentais, tendo o quadro de ansiedade agravado durante o período pandêmico (Machado et al, 2020) e isso pode estar relacionado a diversos contribuintes, como as responsabilidades domésticas, o cuidado familiar (Borges, 2018) e os aspectos fisiológicos femininos, como as variações hormonais e as particularidades genéticas.…”
Section: Discussionunclassified
“…The nal scores can be compared to established cut-off levels in order to assign categories of normal, mild, moderate, severe, and extremely severe. This scale has been frequently used with university students and has been correlated with other variables like addiction to internet and smartphones and the impact of the COVID-19 pandemic (Asif et al 2020; Nugraha et al, 2023).…”
Section: Instrumentsmentioning
confidence: 99%